Climats et premiers peuplements des Alpes du Nord françaises : des derniers chasseurs aux premiers paysans (15 000 à 5 000 ans av. JC.) - Pierre Bintz; Christophe Griggo (Revue de Primatologie)
For nearly 40 years, in mountain massifs of the northern French Alps, research programs have renewed our knowledges of human occupations for late prehistory. Some sites have yielded chrono-cultural and natural sequences of reference. Chronologically fit snugly, they allow a good approach of the cultural developments during the late Upper Paleolithic to the Neolithic and of bioclimats of Oldest Dryas at the Atlantic. To answer the problems of circulation and occupation of the territories, thematic surveys were carried out by researchers from different backgrounds.In the first part are discussed the issues of chronology and palaeoenvironment revealed in particular by studies of animal associations and of vegetal environments.The episodes of prehistoric settlement are presented in a second part. It discusses the terms of the transition from last hunter-gatherers (Magdalenian, Azilian and Mesolithic) to first agro-pastoralists in the Neolithic.In the third part is presented the evolution of major cultural trends across the Western Alps. A map clearly shows the progressive appropriation of the Western Alps from the peripheral regions.